2003
DOI: 10.1073/pnas.1231193100
|View full text |Cite
|
Sign up to set email alerts
|

Effective behavioral treatment of focal hand dystonia in musicians alters somatosensory cortical organization

Abstract: New perspectives in neurorehabilitation suggest that behavioral treatments of movement disorders may modify the functional organization of central somatosensory neural networks. On the basis of the assumption that use-dependent reorganization in these networks contributes to the fundamental abnormalities seen in focal dystonia, we treated 10 affected musicians and measured the concomitant somatosensory changes by using whole-head magnetoencephalography. We found that effective treatment, using the method of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 34 publications
3
91
0
1
Order By: Relevance
“…It may seem difficult to reconcile the observation that upper-limb immobilization may induce dystonia in some patients, while ameliorating dystonic symptoms in others. This point may be even more confusing, as some Authors reported that sensory training by learning to read Braille is an effective treatment for focal hand dystonia (Zeuner et al, 2002) and effective behavioral treatment for dystonia may reverse the abnormalities of cortical sensory maps (Candia et al, 2003). The effectiveness of two opposite behavioral strategies (i.e.…”
Section: Mechanisms Of Motor Cortex Hyperexcitabilitymentioning
confidence: 99%
“…It may seem difficult to reconcile the observation that upper-limb immobilization may induce dystonia in some patients, while ameliorating dystonic symptoms in others. This point may be even more confusing, as some Authors reported that sensory training by learning to read Braille is an effective treatment for focal hand dystonia (Zeuner et al, 2002) and effective behavioral treatment for dystonia may reverse the abnormalities of cortical sensory maps (Candia et al, 2003). The effectiveness of two opposite behavioral strategies (i.e.…”
Section: Mechanisms Of Motor Cortex Hyperexcitabilitymentioning
confidence: 99%
“…In this issue of PNAS, Candia et al (26) describe an orthotic-aided behavioral treatment for focal hand dystonia that apparently reverses the somatosensory map distortions associated with this motor disorder. Somatosensory map normalization is accompanied by a reduction in dystonic symptoms.…”
Section: The Cerebral Cortex Is Shaped Continuallymentioning
confidence: 99%
“…In focal hand dystonia, the boundaries between finger representations are degraded, resulting in cortical regions that represent large skin surfaces crossing multiple digits. In the article by Candia et al (26), sensory motor retuning was used to reduce dystonic symptoms. After the therapy, ''retuned'' maps appeared normalized.…”
Section: The Cerebral Cortex Is Shaped Continuallymentioning
confidence: 99%
“…There are a number of ways in which one can measure the positions and relative rotations of digit segments over time to get kinematic measures such as velocity and acceleration. Candia and colleagues developed a Dexterity Displacement Device 27,28,49,50 to measure velocity profiles of digit displacement during metronome-paced movements of 2 fingers on a device that looks like 2 keys on a keyboard. They then evaluated movement smoothness with the ratio of spectral power in frequency bands near vs outside of the metronome frequency.…”
Section: Resultsmentioning
confidence: 99%